Green Icebergs Revisited. Issue 2 (7th February 2019) - Warren, Stephen G.; Roesler, Collin S.; Brandt, Richard E.; Curran, Mark
Abstract: Ice crystals form in supercooled seawater beneath several Antarctic ice shelves; as they rise to the ice‐shelf base they scavenge particles from the water and incorporate them into the growing basal ice. The resulting marine ice can be ~100 m thick; it differs from sea ice in that it is clear, desalinated, and bubble‐free. Icebergs of marine ice vary in color from blue to green, depending on the nature and abundance of foreign constituents in the seawater that became trapped in the ice as it grew. A red or yellow material (i.e., one that absorbs blue light), in combination with the blue of ice, can shift the wavelength of minimum absorption to green. Previously, dissolved organic carbon (DOC) had been proposed to be responsible for the green color. Subsequent measurements of low DOC values in green icebergs, together with the recent finding of large concentrations of iron in marine ice from the Amery Ice Shelf, suggest that the color of green icebergs is caused more by iron‐oxide minerals than by DOC. These icebergs travel great distances from their origin; when they melt they can deliver iron as a nutrient to the Southern Ocean. Plain Language Summary: Glacier ice, originating from snowfall, flows off the Antarctic Ice Sheet to float on the ocean as ice shelves. At the front of the ice‐shelf, icebergs break off. They appear bluish‐white, intermediate between the blue of pure ice, and the white of snow, because glacier ice contains numerous bubbles that scatter light. Seawater freezes to the base of some ice shelves, forming marine ice, which incorporates organic and inorganic particles from the water. On the resulting composite icebergs, the marine ice can be exposed to view if the iceberg capsizes. The marine‐ice part of such icebergs is clear, dark, and often green in color, because red or yellow particles from the seawater, in combination with the blue of ice, can shift the color to green. Previously, dissolved organic carbon had been proposed to be responsible for the green color. The recent finding of large concentrations of iron in marine ice from the Amery Ice Shelf suggests that the color of green icebergs is caused more by iron‐oxide minerals. These icebergs travel great distances from their origin; when they melt they can deliver iron as a nutrient to the Southern Ocean. Key Points: Icebergs of marine ice vary in color from blue to green The color is probably caused more by iron oxides than by dissolved organic carbon The color may indicate the ability of icebergs to deliver iron as a nutrient